Following the Science by Roger A. Pielke Sr. Issue 1 (19th July 2021) - Pielke, Roger A.
Abstract: The pursuit of basic knowledge and conveying that knowledge for the benefit of society is one of the most rewarding endeavors of life. The opportunity to devote one's professional life to science in order to learn and create new knowledge is intoxicating. This short article highlights some of the aspects of my career that perhaps students and others will find useful, including life experiences that directly affected my career. I also suggest opportunities for major advances in our understanding and predictability of Earth system processes. Plain Language Summary: Whatever path one chooses for a career, success is more likely if you are passionate about the subjects that you work on. I discuss my career path in science in the article. My largest pleasure and achievement are the graduate students and research associates I advised or co‐advised, and who became my colleagues. I was pleased to play a role in their career development and continue to enjoy collaborating with some of them. This is the highest joy and goal of being an academic scientist. Key Points: I share my life experiences as a scientist and educator. I have found that the highest goal of being an academic scientist is in the mentoring of students and younger colleagues This includes encouraging them to think independently, learn outside of their specific disciplinary expertise, and to test and challenge accepted paradigms. My most rewarding research has been on new topics and perspectives that emerge by interacting with colleagues from a wide variety of scientific disciplines I also enjoyed and learned from the international cultural diversity in my chosen field of study. This enriched my life experience